Assessing the factors associated with pedestrian injury in motorcycle-pedestrian crashes in Ghana - Emmanuel Kofi Adanu; Robert Ambunda; William Agyemang; Moses Tefe; Steven Jones (Journal of Traffic and Transportation Engineering (English ed. Online))
In road safety analysis, motorcyclists and pedestrians constitute the most vulnerable road user groups. However, in the interaction between motorcycles and pedestrians, pedestrians tend to be at a greater risk of injury and death. In safety literature, much research has been dedicated to the study of motor vehicle-motorcycle and motor vehicle-pedestrian crashes, and very little research has been done on motorcycle-pedestrian crashes. This study contributes to efforts to fill in the gap in this important safety area from the perspective of a rapidly developing middle-income country, Ghana, where the growth in motorcycle activities has been exponential over the past few years. To achieve this, motorcycle-pedestrian crash data for Ghana from 2015 to 2019 were obtained from the Ghana National Road Traffic Accident database at the Building and Road Research Institute (BRRI) of the Council for Scientific and Industrial Research (CSIR). After cleaning, a total of 2655 motorcycle-pedestrian crash observations were available for analysis and model estimation. The distribution of crashes by severity shows that 16.69% were fatal, 53.10% were incapacitating injuries, and 30.21% were minor injury crashes. The study adopted the random parameters logit with heterogeneity in means and variances approach to develop an injury severity model to understand how various crash factors influence pedestrian injury outcomes. The model estimation results reveal that pedestrians who were struck while crossing the road were more likely to be killed or seriously injured. The likelihood of fatal injury was found to be high at night and when the motorcyclists bolt after hitting a pedestrian. Speeding was also found to be associated with fatal injury outcome. This study is expected to stimulate conversations in the road safety community to pay attention to this silent safety concern. Ultimately, the findings of the study provide data-driven evidence to support countermeasure development and implementation, using the safe systems approach.